Everybody Has a Connection Experience: Prevalence, Confusions, Interference, and Redefinition - Mike Sosteric (Spirituality Studies, 2018)
This paper is an attempt to bring forward awareness of the existence and significance of “connection experiences”, what others call mystical experience, religious experience, and so on. The paper addresses the reality of the experiences, and well as some of the confusions, misconceptions, distortions, and just plain avoidance displayed by sociologists and others.